Implementação de um protótipo de automação residencial voltado para segurança - ALENCAR, Dárlison Souza de (2019)
Technological developments promote the development of more difficult security systems, as traditional methods such as security guards or security companies are subject to failure. The development of this system generates greater safety and effectiveness. The present work refers to the development of a low cost residential access control and monitoring system, which shows signs of movement and status of doors and windows of a home, signaled system changes. For the development of the system, presence sensors, limit switches, microcontroller (nodeMCU ESP32), capacitive keyboard, LCD display, Arduino development platform, Android Studio development platform, a database and a mobile application were used. The adopted system detects movements through a network of sensors installed in a residence module, the data provided by the sensors is sent to the microcontroller that is responsible for processing the information and later used in a connected database. To the mobile app that is responsible for communicating with the user. The system presents satisfactory results, with approximate responses as real time.